Analisis Pengaruh Layanan, Keamanan, dan Kemudahan Penggunaan terhadap Minat Mahasiswa Perbankan Syariah STAIN Mandailing Natal Menggunakan E-Walet Aplikasi Dana - Ridwan, Muhammad; Khalijah, Siti; Siregar, Erpiana (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2024)
This study aims to analyze the influence of Service, Security and Ease of Use on Interest in Using the DANA E-Wallet application. The population of this study were Islamic Banking Students of STAIN Mandailing Natal. The sample used was 99 respondents. The sampling technique for this study used the Purposive Sampling technique. The tool used in this study was SPSS version 20. Based on the results of the SPSS calculation, the Service Feature does not have a positive and significant effect on interest in using. This is evidenced by the t-count value which is smaller than the t table, which is 1.262 <1.661 with a significant value of 0.201> 0.05. While Security has a positive and significant effect on interest in using. This is evidenced by the t-count value of 2.871 which is greater than the t table of 1.661 with a significant value of 0.005 <0.05. And Ease of Use has a positive and significant effect on interest in using. This is evidenced by the calculated t value of 3.507 which is greater than the t table value of 1.661 with a significant value of 0.001 <0.05. Then the results of the study show that Service Features, Security and Ease of Use have a positive and significant effect on interest in using. This is evidenced by the alculated F value of 68.638 which is greater than the F table value of 2.699 with a significant value of 0.000 <0.005.